Vascular lesions as localization factor of acne. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Vasodilation is a localization factor for many dermatological diseases. We recall how atopic dermatitis and psoriasis are often located on salmon patches of the midline. It is not uncommon to find patches of atopic dermatitis even on hemangioma and when the latter is treated with topical beta-blockers the problem of differential diagnosis arises with allergic contact dermatitis (1). On patches of atopic dermatitis and sometimes of psoriasis, Herpes simplex, Coxsachie (2) and molluscum contagiosum virus can be located. Vasodilation linked to sweating plays an important role in the dyshidrosic eczema. Post-traumatic inflammatory vasodilation is characteristically associated with Koebner sign in numerous skin diseases. The role of actinic vasodilation in the Mallorca acne is known, but we have not found in the literature cases of acne vulgaris mainly or exclusively located on vascular lesions.